PENGARUH PENGGUNAAN DOMPET DIGITAL TERHADAP IMPULSIVE BUYING MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN - Marlina, Cici; Ulfah, Maria; Budiman, Jumardi (Universitas Tanjungpura, 2025)
This study aims to determine: (1) the use of digital devices by economics lecturers at the Faculty of Education, Tanjungpura University, (2) the impulsive learning behavior of these lecturers, and (3) the impact of digital media on impulsive behavior. This study uses a quantitative approach with simple linear regression analysis. The sample of this study was 209 students of the 2018- 2021 intake of the Regular A and PPAPK Economics Education Study Programs who were selected randomly. Data collection was carried out using a Google questionnaire. The results showed that (1) 82.83% of economics students used digital devices extensively, which was included in the